Processed Multibeam Sonar Data (version 2) from the Amundsen Sea and Ross Sea acquired during Nathaniel B. Palmer expedition NBP0001 ... - Jacobs, Stan (Interdisciplinary Earth Data Alliance (IEDA), 2003)
This data set was acquired with a SeaBeam Instruments model 2112 multibeam sonar system during Nathaniel B. Palmer expedition NBP0001 conducted in 2000 (Chief Scientist: Dr. Stan Jacobs). These data files include Swath Bathymetry, Acoustic Backscatter data and were processed at sea using the open source MB-System multibeam sonar processing software. Data were acquired as part of the project(s): Glacial History of the Amundsen Sea Shelf; Study of the Circumpolar Deep Water and its Effects on the West Antarctic Ice Sheet and Pine Island Glacier, and funding was provided by the U.S. National Science Foundation. ...